COMPETENCE APPROACH TO ACADEMIC AND PROFESSIONAL TRAINING OF AUDITORS OF INFORMATION SYSTEMS AND TECHNOLOGIES - Олександр Костянтинович Юдін; Андрій Миколайович Черняк; Володимир Юрійович Артемов; Олена Василівна Матвійчук-Юдіна; Вікторія Юріївна Іваннікова (Інформаційні технології і засоби навчання, 2021)
An analysis of the specifics of the formation of a set of of competencies formation for the system of academic and professional training of specialists in audit and monitoring of information systems and technologies is carried out. It is determined that the training system should be formed in accordance with the global system of service industry standardization and international requirements and standards. The essence of the competencies formation on the basis of American and European standards in the field of information systems and technologies is revealed. The hierarchical sequence of the implementation of the world system of standardization for audit and quality control of information systems and technologies functioning in order to determine requirements to competences of the auditor of information technologies is defined. Practical tasks of the process of obtaining objective, qualitative and quantitative assessments of the current state of information infrastructure in accordance with the defined criteria, requirements and quality indicators are highlighted. The main features of competencies, skills, knowledge of specialists in audit and monitoring of information systems and technologies formation are identified. Formation of basic academic and professional competencies of specialists in the audit of information systems and technologies on the basis of the domain educational model Competency Model Clearinghouse is presented. It has been created the competence model for formation of the set of knowledge, skills and abilities during organization and support of information systems and technologies audit, control and monitoring. Tasks and concept of specialists’ integral competence are defined. The list of academic and professional competences is formed, basic abilities and skills of specialists in information systems and technologies audit are defined as well. Classes and levels of competencies are determined, as well as correspondent to them positions in the field of audit of information systems and information technologies of the industry sector. Special attention is paid to the international generally oriented approaches to standardization of educational services and competencies levels in accordance with professional requirements to specialists in the field of information technology audit system. Basic levels of professional certification of information systems auditors, which should provide a high quality level of a wide range of services in the field of information technologies and information security, have been determined.